Good Writing: Rules and Principles (Salam International Academic Journal, 2024)
The most significant legacy we receive from scholars and intellectuals is knowledge. Our predecessors could have trained students to be the heirs of their knowledge instead of writing and composing works. However, they fully understood the importance and vital role of writing in preserving scientific heritage. This recognition led them to engage in writing from an early age.In the past, students aspiring to be writers would study and even memorize books that, in addition to conveying thought and philosophy, were adorned with the elegance of eloquence. Many ancient schools, after the Quran, books such as “Panj Ganj”, “Hafez”, “Bedil”, “Gulistan”, and “Bustan” of Saadi were taught. A deep study of these books elevated the literary talents and passion for writing among seekers of knowledge. However, as journalistic literature began to overshadowed our traditional literary treasures, lengthy yet superficial writings replaced concise but profound ones. In response, some compassionate writers established rules and guidlines for writing principles, focusing on Persian orthography, punctuation, word accentuation, and the handling of foreign terms. The current study follows this same path, but with some insights that are relatively more novel.
Keywords: Writing; Writing Principles; Punctuation; Word Accentuation; Borrowed Words in Language